Assessment of elite junior tennis serve and return practice: A cross-sectional observation. Issue 24 (17th December 2019) - Krause, Lyndon Mark; Buszard, Tim; Reid, Machar; Pinder, Ross; Farrow, Damian
ABSTRACT: Practice tasks that more closely represent the demands of competition are thought to augment skill learning and transfer. This study observed the serve and return performances of junior grand slam tennis and used this benchmark to evaluate the representativeness of serve and return practice among elite junior tennis players. The serve and return behaviour of 26 junior tennis players competing in junior Australian Open grand slam matches were observed and compared with the serve and return practice behaviours of 12 elite junior tennis players over an 8-week period. The variables measured included the number of serves/returns landing in, serve/return type, serve direction and the variability of practised skills. Serve and return practice contributed to <13% of total practice time, with each skill predominately practised in isolation. Compared to the matchplay benchmark, players typically had less success (i.e., fewer serves/returns landing in the court), were less variable in shot selection and hit fewer serves to the extremities of the service box. As task representativeness increased fewer differences between practice and matchplay were observed. Tennis serve and return practice could be improved by better simulating specific competition affordances, providing greater opportunities to practice serve/return tactics and/or increasing the variability of practised skills.